Community Engagement: A Case Study Comparison of Social Enterprise and Corporation Strategies - Kamusiime, Jackie .D. (2012)
Social Enterprises are organisations that exist to serve social objectives primary to seeking financial returns (Dacin, 2011). The economic rent obtained from their operations is reinvested back into the enterprise to pursue social missions. On the other hand, corporations are organisations that exist with the primary responsibility of increasing their shareholder’s value (Friedman, 1970). However, since the 1950s (Carroll, 1999) corporations have gradually awakened to considering the needs of the larger society in which they exist through corporate social responsibility.